Contests with multi-tasking; Contests with Multi-Tasking - Derek Clark; Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
The standard contest model in which participants compete in a single dimension is well understood and documented. Multi-dimension extensions are possible but are liable to increase the complexity of the contest structure, mitigating one of its main advantages: simplicity. In this paper we propose an extension in which competition ensues in several dimensions and a competitor that wins a certain number of these is awarded a prize. The amount of information needed to run the contest is hence limited to the number of dimensions won by each player. We look at the design of this contest from the point of view of maximizing effort in the contest (per dimension and totally), and show that there will be a tendency to run small contests with few dimensions. The standard Tullock model and its results are encompassed by our framework. – – Die Arbeit untersucht Wettbewerbsstrukturen, in denen die Teilnehmer eines Turniers in mehr als einer beobachtbaren Dimension oder Outputgröße miteinander konkurrieren, und in denen ein Wettbewerber einen Preis gewinnt, wenn er hinsichtlich einer vorgegebenen Anzahl von Dimensionen besser als seine Konkurrenten abschneidet. Es zeigt sich dabei, dass ein Turnierveranstalter, der die Anstrengungen der Turnierteilnehmer maximieren möchte, Turniere mit einer kleinen Anzahl von Outputdimensionen bevorzugen sollte.
Keywords: D72; 330; contest design; multi-tasking; effort incentives